Patient -controlled epidural ropivacaine as a post-Cesarean analgesia: A comparison with epidural morphine - Li-Kuei Chen; Pei-Lin Lin; Chen-Jung Lin; Chi-Hsiang Huang; Wan-Chi Liu; Shou-Zen Fan; Mao-Hsien Wang (Elsevier, 2011)
Objective: Conventional, intermittent, epidural morphine is widely applied as a post-Cesarean delivery analgesia. We compared the analgesic efficacy, motor weakness, and side effects of administering a patient-controlled epidural analgesia (PCEA) of pure ropivacaine versus the intermittent administration of epidural morphine after Cesarean delivery. Materials and Methods: This randomized, double-blind study included 120 full-term parturients who underwent elective Cesarean delivery and received either PCEA with pure ropivacaine or an intermittent bolus epidural of 2 mg/10 mL morphine in normal saline twice per day. The efficacy of pain relief, post-Cesarean side effects, motor blockades, time to first ambulation, and global satisfaction scores were evaluated. Results: Pain scores were recorded at the four evaluation times (2, 12, 24, and 48 hours post-Cesarean delivery), and the time to first ambulation did not statistically differ between the two groups. Patients in the ropivacaine group experienced more motor weakness at 2 and 12 hours, fewer side effects, and higher global satisfaction scores than those in the morphine group (p < 0.05). Conclusion: The analgesic efficacy after cesarean delivery was almost equivalent between two groups. PCEA with pure ropivacaine induced significant motor blockade during the first 12 hours, but without delaying the time to first ambulation. Patients in the ropivacaine group reported higher patient satisfaction scores due to the significant reduction of annoying side effects, such as pruritus, nausea, vomiting, and urinary retention.